Use of botulinum toxin in children with cerebral palsy - Monika Stecko; Agata Wawryków; Katarzyna Korabiusz; Magda Fraszczyk; Agnieszka Kordek (Kazimierz Wielki University, 2019)
Cerebral palsy in children is a syndrome of disorders resulting from damage to the central nervous system in its early development [1]. Damage to the structure of the upper motor neuron during its early development leads to dysfunction of the central motor control system and, consequently, to impairment of the child's functional development [2,3]. The consequences of damage to the central motor control system include the presence of muscular tension disorders, especially spasticity [4,5]. Botulinum toxin is one of the many pharmacological agents used to reduce spasticity. Botulinum toxin therapy is one of the most effective and currently safest methods for the treatment of spasticity in children [6].